EFEKTIVITAS IMPLEMENTASI PROGRAM ELECTRONIC TRAFFIC LAW ENVORCEMENT (ETLE) NASIONAL DALAM PENINGKATAN PELAYANAN PUBLIK DI KOTA PEKANBARU - Endah Syafitri; Dadang Mashur (Cross-border, 2022)
Problems on the road that are increasing, such as the increase in the number of accidents, the threat to the safety of other road users, and the emergence of a culture or habit of violating traffic must be resolved immediately. With the development of science and technology, the Indonesian National Police presents the Electronic Traffic Law Enforcement or ETLE to solve the problem of enforcing traffic violations. Where one of the implementers of ETLE is Riau Province, precisely in Pekanbaru City which was inaugurated in April 2021. In the process of implementing ETLE, it was found that it was running effectively which was supported by various parties starting from the local government level and the community as well as the capacity of the implementing agency. However, there are inhibiting factors in the form of network access that is still hampered, public knowledge is still minimal regarding ETLE and the timeliness of reporting from the ETLE Task Force to the District Court. This study uses a qualitative method with a case study approach which uses data collection techniques in the form of interviews, observations and documents. The source of this research was obtained from the ETLE implementor and the target of the ETLE implementation, namely the community.